Information on untyped variation in genome-wide association studies - Nicolae, Dan (Henry Stewart Talks, 2007)
Genome-wide association studies, Methods for testing untyped variation, Coverage of commonly used platforms, Multilocus linkage disequilibrium, TUNA: testing untyped alleles, Accuracy of imputation, Indirect methods for structural variation
Archived at 2021/02/25